K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 5 2017

\(sin^6a+cos^6a+3sin^2a.cos^2a=sin^6a+cos^6a+3sin^2a.cos^2a\left(sin^2a+cos^2a\right)\)

\(=\left(sin^2a+cos^2a\right)^3=1\)

1 tháng 7 2018

E = sin^6 + cos^6 + 3sin^2.cos^2

= (sin^2 + cos^2)(sin^4 - sin^2.cos^2 + cos^4) + 3 sin^2.cos^2

= (sin^2 + cos^2)^2 - 3sin^2.cos^2 + 3sin^2.cos^2

= 1

26 tháng 7 2017

Kết quả:

A=1    B=2   C=-4

3 tháng 10 2018

\(A=\sin^6\alpha+cos^6\alpha+3\sin^2\alpha\cos^2\alpha\left(\sin^2\alpha+\cos^2\alpha\right).\)vì\(\sin^2\alpha+\cos^2\alpha=1\)

\(=\left(\sin^2\alpha+\cos^2\alpha\right)^3=1^3=1\)

\(B=2\left(\cos^2\alpha+\sin^2\alpha\right)=2.1=2\)

\(C=\frac{-4\cos\alpha\sin\alpha}{\sin\alpha\cos\alpha}=-4\)

25 tháng 4 2023

Này là kiến thức lớp 10 mà bạn...

27 tháng 8 2021

a/ \(A=\frac{cot^2a-cos^2a}{cot^2a}-\frac{sina.cosa}{cota}\)

\(=\frac{\frac{cos^2a}{sin^2a}-cos^2a}{\frac{cos^2a}{sin^2a}}-\frac{sina.cosa}{\frac{cosa}{sina}}\)

\(=\left(1-sin^2a\right)-sin^2a=1\)

27 tháng 8 2021

b/ \(B=\left(cosa-sina\right)^2+\left(cosa+sina\right)^2+cos^4a-sin^4a-2cos^2a\)

\(=cos^2a-2cosa.sina+sin^2a+cos^2a+2cosa.sina+sin^2a+\left(cos^2a+sin^2a\right)\left(cos^2a-sin^2a\right)-2cos^2a\)

\(=2+\left(cos^2a-sin^2a\right)-2cos^2a\)

\(=2-sin^2a-cos^2a=2-1=1\)

a, ta có \(\cos^2\alpha\)+  \(\sin^2\alpha\)= 1

                  1/5 + \(\cos^2\alpha\)= 1

                               \(\cos^2\alpha\)= 4/5

\(4\cos^2\alpha\)+6 \(\sin^2\alpha\)= 4 . 4/5 + 6.1/5=22/5

b, \(\sin\alpha\)= 2/3 

\(\sin^2\alpha\)= 4/9

\(\cos^2\alpha=\frac{5}{9}\)

\(5\cos^2\alpha+2\sin^2=\frac{5.5}{9}+\frac{2.4}{9}=\frac{33}{9}\)

#mã mã#